Pengaruh Persepsi Atas Biaya Kuliah Dan Kualitas Layanan Terhadap Prestasi Belajar Mata Kuliah Statistik - Permana, Adi; Yusup, Ayi Maulana; Nurhayati, Nurhayati (Jurnal Ekualisasi, 2024)
The purpose of this study was to determine the direct effect of perceptions of tuition fees on student achievement, to determine the direct effect of service quality on academic achievement and to find out the indirect effect of perceptions of tuition fees on student achievement through service quality. This research uses a quantitative method with a path analysis approach in which service quality is the intervening variable. Data were obtained by distributing research questionnaires in the form of perception questionnaires on tuition fees and service quality with rating scaling following the Linkert rules. Meanwhile, the study achievement data for statistics courses were obtained from UTS scores. The number of samples in this study were 72 students who were taken by random sampling technique. Based on the results of the study it was concluded that there is a positive and significant direct effect of perceptions of tuition fees on learning achievement, there is a positive and significant direct effect of service quality on learning achievement and there is a positive and significant indirect effect of perceptions of tuition fees on student achievement through service quality